Aplicação do Índice de Aridez e Índice de Vegetação por diferença normalizada para análise da susceptibilidade à desertificação no município de Irauçuba – CE. - Abreu, Thaís Carvalho de (2018)
The present research project has as main objective the application of the aridity and vegetation indexes by normalized difference for the temporal analysis of the susceptibility to desertification in the city of Irauçuba / CE, through the use of geoprocessing to assist in the environmental management of the object of study. The level of desertification in the districts of the municipality of Irauçuba was characterized by the Aridity Index. In addition, a temporal analysis of the normalized difference vegetation index (NDVI) was carried out to evaluate where mitigating and preventive actions should be concentrated, in addition to proposing some of these actions. For this, the software Quantum Gis 3.0.1 was used for the elaboration of the maps, images from the satellite Landsat 4-5 and Landsat 8 sensor Thematic Mapper - TM, besides information of the pluviometria of the municipality. The satellite image processing for NDVI calculation was efficient and accurate for the classification of the vegetation cover situation of the city of Irauçuba - CE. In this study the NDVI was more efficient than the Aridity Index, since its results are more specific regarding the spatialisation, and thus different preventive and mitigating activities can be focused according to the local needs and characteristics, in smaller areas, thus saving resources for example. The Aridity Index is advantageous in the analysis of older data, given the absence of satellite images.